Pengaruh Pendidikan Karakter dan Motivasi Belajar terhadap Disiplin Belajar Siswa Sekolah Menengah Pertama (SMP) pada Mata Pelajaran IPS Terpadu - Renaldi Abdul; Meyko Panigoro; Mamang Kasim; Radia Hafid; Abdulrahim Maruwae (Lembaga Pengembangan Kinerja Dosen, 2026)
The purpose of this study was to determine the effect of character education and learning motivation on student learning discipline in Integrated Social Studies subjects for class VIII at SMP Negeri 3 Limboto, Gorontalo Regency. This study used a quantitative approach with a quantitative descriptive research method. The data used were primary data obtained through distributing questionnaires to 50 class VIII students as respondents, and supported by research documentation. Data analysis was carried out using multiple linear regression to test the relationship between the variables of character education, learning motivation, and student learning discipline. The results showed that character education had a positive and significant influence on student learning discipline, as evidenced by the calculated t value of 2.698 which was greater than the t table of 1.677 and a significance value of 0.010 which was less than 0.05. In addition, learning motivation also showed a positive and significant influence on learning discipline with a calculated t value of 3.386 which was greater than the t table of 1.677 and a significance value of 0.001 which was less than 0.05. Simultaneously, character education and learning motivation have a significant effect on student learning discipline, which can be seen from the calculated F value of 92.162 which is greater than the F table of 3.19 and the significant probability value of 0.000 which is less than 0.05. The coefficient of determination (R²) of 0.797 indicates that 79.7% of the variation in student learning discipline can be explained by these two variables, while the remaining 20.3% is influenced by other factors outside this study. Thus, increasing character education and learning motivation in schools is expected to improve student discipline which has implications for better academic quality and character formation.